Impact of delisting high‐strength opioid formulations from a public drug benefit formulary on opioid utilization in Ontario, Canada. Issue 5 (14th March 2019) - Martins, Diana; Khuu, Wayne; Tadrous, Mina; Juurlink, David N.; Mamdani, Muhammad M.; Paterson, J. Michael; Gomes, Tara; ,
Abstract: Purpose: High‐strength opioid formulations were delisted (removed) from Ontario's public drug formulary in January 2017, except for palliative patients. We evaluated the impact of this policy on opioid utilization and dosing. Methods: We conducted a longitudinal study among patients receiving publicly funded, high‐strength opioids from August 2016 to July 2017. The primary outcome measure was weekly median daily opioid dose (in milligrams of morphine or equivalent; MME) of (1) publicly funded and (2) all opioid prescriptions irrespective of funding source, evaluated using interrupted time series analyses and stratified by palliative care status. Results: Following policy implementation, the weekly median daily dose of publicly funded opioids decreased immediately among non‐palliative patients by 10 MME (95% confidence limit [CL], −16.8 to −3.1) from a pre‐intervention dose of 424.5 MME (95% CL, 417.8‐431.2) and fell gradually among palliative patients by 3.9 MME per week (95% CL, −5.5 to −2.3) from a pre‐intervention dose of 450.1 MME (95% CL, 432.5‐467.7). In contrast, among all opioid prescriptions, gradual reductions in weekly median daily doses were observed only for non‐palliative patients, which decreased by 0.7 MME per week (95% CL, −1.3 to −0.2) from a pre‐intervention dose of 426.2 MME (95% CL, 420.9‐431.5). Conclusion: The delisting of publicly‐funded, high‐strength opioids was accompanied by changes in funding source and small reductions in the weekly median daily doses dispensed. Although observed dose reductions of less than 1 MME weekly are likely not clinically relevant, safety implications of these changes require further monitoring.